Turismo e desenvolvimento econômico regional - Henz, Aline Patrícia (2021)
Since 2004 the planning of tourism in Brazil is guided by the Regionalization Program (TRP), which aims to implement a decentralized, coordinated, integrated and articulated public management among the spheres of public power, private initiative and society. The Program justifies that cooperation among the cities can generate more effective results compared to isolated actions, with the objective of structuring and diversifying the tourist offer to expand the sector's productive chain, based on the socioeconomic insertion of the local population, especially in the generation of jobs. On the contrary, the literature review on the investigated theme in different regions of the country pointed out that the TRP does not present the expected results and has not instituted an evaluation and monitoring model for tourist regions. Given the above, the general objective of the thesis was to analyze the PRT as a development strategy for the sector in the Touristic Region of Cataratas do Iguaçu and Caminhos ao Lago de Itaipu, located in the Western Paraná Geographic Region and formed by 19 cities. As a theoretical contribution, three theories of regional economic development were used to support the analysis: The Strategy of Economic Development Theory - linkages (HIRSCHMAN, 1961), Circular Cumulative Causation Theory (MYRDAL, 1968) and Export-Base Theory (NORTH, 1977). From the triangulation method with the subjects represented by the Theoretical Referential, Literature Review and Documentary Research, two study Dimensions were established, which were broken down into two Indicators, represented by twelve Variables. Regarding the objectives, the research is characterized as applied and descriptive and regarding the approach to the problem, as qualitative and quantitative, with the use of three techniques: a) descriptive statistics to characterize the formal employment in the tourism sectors in the cities of the region from 1998 to 2019; b) application of a questionnaire to municipal tourism managers to investigate aspects related to the management of the PRT; c) hierarchical cluster analysis to discuss the formation of the region under study with the use of new variables. As results of the qualitative research, it was possible to confirm the inexistence of planning tools, such as the Tourist Inventory and the Municipal Tourism Plan; lack of qualified technical labour in the municipal public management; low budget for tourism; lack of articulation between public and private agencies, due to the discontinuity or inexpressive performance of Municipal Councils of Tourism; low support from entrepreneurs and the local population; low offer of tourist attractions; absence of a regional product and strategic planning, besides the lack of integration among the cities. According to the managers that answered the survey, the benefits of the PRT are limited to the marketing actions carried out by the Regional Governance and by the receipt of resources from the Ministry of Tourism. The cities still do not understand its function in the region, even because it was evident that tourism is not a priority sector. The descriptive statistics technique showed an annual growth of 4.18% in formal jobs in the tourism sector in the study Touristic Region and 3.94% in establishments. However, formal employment and establishments in tourism sectors in the cities showed low variation in the TRP period between 2004 and 2013. The percentages of growth mainly were less than 10%. The Location Quotient (LQ) indicated a reduction in the number of cities specializing in tourism from 1998 to 2019, with six identified in the first period and three for the last analysis period. The municipality that showed the best performance in all variables (jobs, establishments, and LQ) was Guaíra, with higher relative growth than Foz do Iguaçu. The hierarchical cluster analysis used the Euclidean Squared Distance measure and the Ward method. The results indicated the formation of six clusters, which were analyzed by the classification of the Tourism Policy of Paraná in tourism destinations and with tourism potential. The result of the variables selected for 2019 indicated Foz do Iguaçu as a tourism destination and Céu Azul; Entre Rios do Oeste; Guaíra; Itaipulândia; Marechal Cândido Rondon; Medianeira; Santa Helena, and Santa Terezinha de Itaipu as cities with tourism potential. Thus, the region would be formed by nine cities, not 19 as presented by the Ministry of Tourism, and the other cities do not present relevance in the variables, therefore, with no need to remain on the Brazilian Tourism Map. Such results can contribute to the optimization of public resources distributed to the cities inserted in tourist regions.